Neural mechanisms of treatment for mental disorders - Shalabi, Abdulrhman (2023)
“Cognitive control” refers to the ability to regulate thoughts and actions in the service of goals or plans (Braver, 2012). Coordination between the central and peripheral autonomic nervous systems (ANS) maintains arousal and attention levels, which are essential for effective cognitive control. Diamond (2013) proposed a cognitive control model that builds on three core cognitive functions: cognitive flexibility, inhibitory control, and working memory. Abnormality in active inhibitory cognitive control is implicated in a broad range of psychiatric and personality disorders, including schizophrenia, attention deficit hyperactivity disorder (ADHD), impulsivity, and substance abuse, among many others. Transcranial direct current stimulation (tDCS) and cognitive training are two neuromodulation techniques which have the potential to modulate cortical functions to introduce long-lasting neuronal plasticity. The antisaccade task is a visual inhibitory control task frequently used to assess cognitive control. It requires the participant to suppress an automatic stimulus-driven saccadic eye movement and instead make a goal-driven saccade in the opposite direction.